Millennial money makeover : escape debt, save for your future, and live the rich life now - Richardson, Conor (Career Press, 2019)
"A financial guide for the American millennial. A relatable, easy-to-read, sequential, and comprehensive approach to paying off debt, building an automated savings system, buying life's early stage big purchases, and teaching readers how to live the true millionaire lifestyle"--